Divorce Due To Apostasy (Study of Differing Decisions in Religious Courts) - Dzurrotul Muniroh Ahdaniah; Sri Lumatus Sa’adah; Muhammad Faisol (Green Publisher Indonesia, 2024)
The case of divorce due to apostasy is a civil case that is not directly regulated in Indonesian legislation. Therefore, there are differing decisions in cases of divorce due to apostasy. In the divorce case No. 0333/pdt.G/2013/PA.Bdw, with the reason of the husband's apostasy, the court issued a decision of talak bain sughra, while in the divorce case No. 3/pdt.G/2019/PA.Bky, with the same reason, the court issued a decision of fasakh. The research method used is a normative method with a statutory approach. The researcher employs descriptive analysis in discussing relevant theoretical studies related to divorce due to apostasy. The findings of this research are: 1) the legal considerations of the judges in the cases No. 0333/pdt.G/2013/PA.Bdw and No. 3/pdt.G/2019/PA.Bky were not appropriate and should have referred to KHI article 116 letter k. 2) the judges' decisions in the cases No. 0333/pdt.G/2013/PA.Bdw and No. 3/pdt.G/2019/PA.Bky were in accordance with the maqasid shariah in terms of preserving religion because both decisions terminated the marriage bond, either through talak bain sughra or through fasakh.